The influence of Ezekiel in the Fourth Gospel: intertextuality and interpretation - Fowler, William G. (Biblical interpretation series, 2018)
Intro -- Contents -- Preface -- Abbreviations -- Chapter 1 Introduction -- 1 In Search of the Background to the Fourth Gospel -- 2 Intertextuality and Interpretation -- 3 The Johannine Community and Ezekiel -- 4 Prior Research into the Inter-relatedness of Ezekiel and the Fourth Gospel -- 5 Critical Issues -- 5.1 Authorship -- 5.2 Relationship to the Apocalypse -- 5.3 Unity and Order of Composition -- 5.4 Historicity -- 6 Methodology -- 7 Presentation -- Chapter 2 The Theological Vocabularies of John and Ezekiel -- 1 Words Used by John Fifty Times or More -- 1.1 Father -- 1.2 Believe -- 1.3 Know -- 1.4 World -- 1.5 Send -- 1.6 Hear -- 1.7 Love -- 1.8 Life -- 2 Words Used in the "I Am" Sayings -- 2.1 Bread -- 2.2 Light -- 2.3 Door -- 2.4 Shepherd -- 2.5 Resurrection -- 2.6 Way -- 2.7 Truth -- 2.8 Vine -- 3 Other Significant Words and Phrases -- 3.1 Word -- 3.2 Witness -- 3.3 Glory -- 3.4 Judgment -- 3.5 Water -- 3.6 Spirit -- 3.7 Signs -- 4 Conclusions -- Chpater 3 Primary Points of Contact -- 1 The New Temple -- 1.1 The Replacement, or Embodiment, of Judaism? -- 1.2 Jewish Expectations -- 1.3 Ezekiel's New Temple -- 1.4 Jesus as the New Temple -- 1.5 Parallels -- 1.6 Conclusions and Implications -- 2 Rivers of Living Water -- 2.1 The Feast of Tabernacles -- 2.2 Punctuation and Antecedent of αὐτοῦ -- 2.3 Scripture Citation -- 2.4 Conclusions and Implications -- 3 The Good Shepherd -- 3.1 The Setting of John 10 -- 3.2 Old Testament Imagery -- 3.3 Ezekiel's Shepherd -- 3.4 The Good Shepherd in John's Gospel -- 3.5 Comparisons and Conclusions -- 4 The Resurrection -- 4.1 Chapter 5 as Precedent to Chapter 11 -- 4.2 The Resurrection and the Life, John 11 -- 4.3 Ezek 37 and the Valley of Dry Bones -- 4.4 Comparisons and Conclusions -- Chapter 4 Secondary Points of Contact -- 1 Born of Water and Spirit -- 2 Son of Man -- 3 Paraclete